Analisis Efisiensi Dan Efektivitas Penggunaan Anggaran Pemeliharaan Jembatan Pada Dinas Pekerjaan Umum Kabupaten Ende - Katarina Meo; Yulita Londa; Nuraini Ismail (ANALISIS, 2020)
The purpose of this study is to analyze the efficiency and effectiveness of the use of the bridge maintenance budget for the public works service of Ende district from 2015-2017. The data analysis used is quantitative analysis by calculating the efficiency and effectiveness of the bridge maintenance budget. The research has the character of explaining matters relating to hypothesis testing and in its descriptive nature it also contains descriptions used in the research, namely by collecting data. The data collected in this study are the bridge construction budget data from 2015-2017 which were obtained from the Public Works Office of Ende Regency and data regarding the physical realization and realization of the district bridge construction budget in Ende Regency at the Public Works Office. The results of this study indicate that the budget and physical realization greatly influence the efficiency and effectiveness of bridge construction.